The Contribution of the Surabaya State University Library in Promoting Open Access Information Sources - Hariyati, Mutty; Awaliatul Ma'rifah; Ramadhani, Humayyun Nabila; Hudiana, Aden Aris (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the problem: Library, as a part of universities that create institutional scientific works bears responsibility for serving as both the central database for the scientific publications the library subscribes to and a platform for the management of institutional scientific works. Open access facilitates simpler access to and use of information while hastening the process of information distribution. Purpose: The purpose of this study is to determine how university libraries support open access information sources. Method: In this study, interviews were employed to collect data using a qualitative research methodology. Findings: The data indicated that libraries and librarians promoted the availability of OA information sources through the library page, which can be viewed at https://library.unesa.ac.id. Conclusion: To ensure that lecturers and students have access to a variety of scientific information sources, it is crucial for university libraries to develop and promote open access information sources.